Lansia Aktif dan Berdaya: Studi Perilaku Prososial pada Kader Surabaya Hebat - Widya Annisa Royani; Cicilia Larasati Rembulan (Jurnal Psikologi Perseptual)
The late adult population is increasing, but they are seen as a burden by society. However more than half of the elderly population is still working, such as volunteers. This study aims to identify the forms of prosocial behaviour, motivations of prosocial behaviour, and benefits of prosocial behaviour among late adults of Kader Surabaya Hebat. The research method used was qualitative with an instrumental case study design. Participants were selected using purposive sampling technique, with characteristics of Surabaya Hebat cadres who have been active for at least 2 years in Lontar Village Surabaya, aged 60 years and above. Data collection was conducted by pre-survey, interview, and documentation. Data was analysed using thematic analysis technique. The results showed that the form of prosocial behavior in late adult cadres was helping residents, assisting cadres in task execution and guiding young The motivation of elderly cadres to do prosocial behaviour comes from 3 sources, such as intrinsic, extrinsic and situational. The benefits of prosocial behavior for late adults are getting positive feelings, increasing knowledge and experience, adding relationships, improving health and getting incentives. This research also found that religiosity and cultural factors influence prosocial behaviour, as well as the importance of relationships in prosocial behaviour. The implication of this research is to increase awareness of the elderly, also for the Kader Surabaya Hebat coordinator and the government to provide support for the late adult to be productive.